2019
DOI: 10.20473/mog.v26i32018.123-127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of per oral cypermethrin exposure on Bcl-2 expression in granulose cells and antral follicle count of Rattus norvegicus ovaries

Abstract: ABSTRAKObjectives: To determine the effect of oral cypermethrin exposure on the decrease of Bcl-2 expression in granulosa cells and antral follicle count in Rattus norvegicus ovary. Materials and Methods:This was a true experimental study using post-test control group design. This study used 24 Rattus norvegicus which were divided into 4 groups, the control group, treatment group (P1) exposed to cypermethrin 10 mg/kg BW, treatment group (P2) exposed to cypermethrin 15 mg/kg BW and treatment group (P3) exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Several prior reports [29,[50][51][52] presented parallel results from our study, where CYP induced apoptosis and upregulated p53 and Cas3 gene expression besides the down-regulation of Bcl2 expression in neuronal cell and testis tissue. Also, studies of Molavi et al [53] and Indrayanti et al [43], which revealed that CYP induced RNA damage and over-expression of Cas3 and p53 in granulosa and theca cells besides decreased expression of Bcl-2 in the ovaries of CYP exposed group, are in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Several prior reports [29,[50][51][52] presented parallel results from our study, where CYP induced apoptosis and upregulated p53 and Cas3 gene expression besides the down-regulation of Bcl2 expression in neuronal cell and testis tissue. Also, studies of Molavi et al [53] and Indrayanti et al [43], which revealed that CYP induced RNA damage and over-expression of Cas3 and p53 in granulosa and theca cells besides decreased expression of Bcl-2 in the ovaries of CYP exposed group, are in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Bcl-2 is one member of the Bcl-2 antiapoptosis protein family. If the anti-apoptotic protein is lower than the pro-apoptotic protein then apoptosis will occur [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation